2019
DOI: 10.3390/ma12142239
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability and Flammability Behavior of Poly(3-hydroxybutyrate) (PHB) Based Composites

Abstract: A series of samples based on poly(3-hydroxybutyrate) (PHB) containing five different additives were prepared and their thermal stability and flammability were discussed. The samples first underwent flammability screening by using Pyrolysis Combustion Flow Calorimeter (PCFC) analyses. Then, four samples were selected for further investigations. PHB composites containing sepiolite (Sep.) inorganic nanofiller, and also organic ammonium polyphosphate (APP) were examined for flammability and thermal behavior using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 39 publications
(44 reference statements)
3
31
1
Order By: Relevance
“…Thermal analyses showed that the extracted PHB existed as a thermally stable semi-crystalline polymer 55 , the T m and T g of extracted PHB were 171.8 and 4.03 °C, respectively. Similar T m and T g have been previously reported in PHB 63 65 . The maximum thermal decomposition observed was at 288 °C by FIIR and is related with the ester cleavage of PHB by b-elimination reaction 67 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thermal analyses showed that the extracted PHB existed as a thermally stable semi-crystalline polymer 55 , the T m and T g of extracted PHB were 171.8 and 4.03 °C, respectively. Similar T m and T g have been previously reported in PHB 63 65 . The maximum thermal decomposition observed was at 288 °C by FIIR and is related with the ester cleavage of PHB by b-elimination reaction 67 .…”
Section: Discussionsupporting
confidence: 90%
“…The maximum thermal decomposition observed was at 288 °C by FIIR and is related with the ester cleavage of PHB by b-elimination reaction 67 . Many researchers have been reported similar TGA results of PHB 55,[63][64][65][66] . All these results confirmed that the polymer produced by R. pyridinivorans BSRT1-1 is PHB homopolymer, and the properties of extracted PHB were similar to the commercial PHB 68 .…”
Section: Discussionmentioning
confidence: 62%
“…The blends with different contents in P(3HB- co -3HV- co -3HHx) presented the maximum of melting in the range of 169–174 °C with ∆H m values of 74 and 68 J/g for the film samples with 10 and 25 wt% of terpolymer, respectively, whereas the films with 50 wt% of terpolymer showed a value of 43 J/g. As it can also be observed in the DSC curves, the neat P(3HB- co -3HV- co -3HHx) presented a very complex melting behavior, exhibiting the highest endothermic peaks at 111 °C, ascribed to the lowest crystalline density fractions of the terpolymer [ 59 , 60 ], and at 173 °C, for the most thermodynamically stable 3HB-rich fractions [ 61 ]; and having a whole ∆H m value of 33 J/g. Thus, in the blend samples, a drop in T m and ∆H m was generally observed when P(3HB- co -3HV- co -3HHx) was incorporated into PHBV.…”
Section: Resultsmentioning
confidence: 90%
“…The diffractograms, included in Figure 4 , revealed two main peaks located at 13.6 and 17.0° 2θ, corresponding to the (020) and (110) lattice planes of the orthorhombic unit cell of PHB [ 67 ]. These intense peaks were followed by three other minor reflections centered at approximately 22.6, 25.8, and 26.9° 2θ, which originate from (111), (121), and (040) lattice planes [ 61 , 68 ]. The diffraction peaks found here agree well with those reported in the literature, where the crystal lattice of PHBV with 3HV contents below 30 mol% corresponds to the unit cell of PHB [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the synthesis of conventional PUs, polyols and isocyanates are usually derived from petrochemical sources. Over recent decades, growing concerns about global warming resulting from human activity, depletion of fossil resources, and fluctuating oil price has prompted debate among researchers exploring bio-based resources to replace starting chemicals with green, sustainable, and renewable sources [ 10 , 11 , 12 , 13 , 14 ]. Thus, biopolymers derived from biological and renewable sources have attracted the attention of researchers due to their sustainability, abundant availability, and eco-friendliness [ 4 ].…”
Section: Introductionmentioning
confidence: 99%